098. Report in Emergency repair for Duodenum Part 1 Perforation in Referral Hospital Banyumas - Hanif, Ahmad Shafa; Handaya, Adeodatus Yuda; Bassyarah, Yusuf Arif (JBN (Jurnal Bedah Nasional), 2024)
Introduction : Duodenal perforation was frequent cause of hollow viscus perforation beside to gastric perforation. Immediate source control properties, reproducibility, simplicity and applicability was the prefer method in emergency setting to repair this perforation. Case : We present one case of female, 46 years old patient with duodenal part 1 perforation with Boey Score 1, where we performed repair with primary suturing, gastrojejunal – braun anastomosis and omental patch. We found part 1 duodenal perforation 1.5cm in diameter. Patient was in hospital for 5 days before being discharged. Conclusions : Primary suturing, gastrojejunal – braun anastomosis and omental patch applicable in referral hospital, were preferable method that has best result and easy repair technique based on this report.